Reasoning in a multicultural society - Adian, Donny Gahral (UI Scholars Hub, 2011)
Multicultural society as a way of being-with-others needs a certain form of public reasoning. Unfortunately, the current yet dominant form of public reasoning is infiltrated by biases from occidental culture. This mode of reasoning does nothing but uproot participants from their cultural identity for the sake of universal consensus. Multicultural society, however, consists of identities which are embedded in the individuals' cultural tradition. This sociological fact demands a richer form of rationality that does not deny the multiplicity of cultural values and embedded identities. We need a form of public reasoning which emphasizes cultural understanding rather than abstract consensus. We might call it a multicultural, contextualized and other-regarding form of public reason.